Predictors of tumor progression of low-grade glioma in adult patients within 5 years follow-up after surgery - Yan, Zhiqiang; Wang, Jiang; Dong, Qiufeng; Zhu, Lian; Lin, Wei; Jiang, Xiaofan (Frontiers in Surgery, 2022)
Background Glioma originates from glial cells in the brain and is the most common primary intracranial tumor. This study intends to use a retrospective analysis to explore the factors that can predict tumor progression in adult low-grade gliomas, namely WHO II grade patients, within 5 years after surgery. Methods Patients with WHO grade II glioma who were surgically treated in our hospital from February 2011 to May 2017 were included. According to the inclusion and exclusion criteria, 252 patients were included in the final analysis. According to the results of the 5-year follow-up (including survival and imaging review results), patients were divided into progression-free group and progression group. Univariate and multivariate analysis were conducted to investigate the related factors of tumor progression during the 5-year follow-up. Results The results of the 5-year follow-up showed that 111 (44.0%) cases had no progress (progression free group, PFG), 141 (56.0%) cases had progress (progression group, PG), of which 43 (30.5%) cases were operated again, 37 cases (26.2%) received non-surgical treatments. There were 26 (10.3%) all-cause deaths, and 21 (8.3%) tumor-related deaths. Univariate and multivariate analysis showed that age >45 years old (OR = 1.35, 95% CI, 1.07–3.19, P = 0.027), partial tumor resection (OR = 1.66, 95% CI, 1.15–3.64, P = 0.031), tumor diameter >3 cm (OR = 1.52, 95% CI, 1.14–4.06, P = 0.017) and no radiotherapy (OR = 1.37, 95% CI, 1.12–2.44, P = 0.039) were independent predictors of the progression of tumor during the 5-year follow-up period. Conclusion Age >45 years old, partial tumor resection, tumor diameter >3 cm, no radiotherapy are predictors for tumor progression for glioma patients after surgery.